2005
DOI: 10.1038/sj.bmt.1704779
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell mobilization with intravenous melphalan and G-CSF in patients with chemoresponsive multiple myeloma: report of a phase II trial

Abstract: Summary:Multiple myeloma (MM) is an incurable hematologic malignancy for which autologous hematopoietic stem cell transplantation (HCT) is a standard therapy. The optimal method of stem cell mobilization is not defined. We evaluated intravenous melphalan (60 mg/m 2 ), the most effective agent for MM, and G-CSF (10 lg/kg/day) for mobilization. End points were safety, adequacy of CD34 þ collections, MM response, and contamination of stem cell components (SCC). In total, 32 patients were mobilized. There were no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Compared with mobilization regimens using G-CSF alone, chemomobilization is associated with increased morbidity, greater risk of infection, more hospital admissions, transfusions, antibiotic therapy and considerably greater cost overall. 29,[39][40][41][42] Although treatment-related mortality is rare, significant morbidity related to neutropenia that can often require hospitalization has been described, and many reports point to greater resource utilization with chemomobilization than with cytokine-alone mobilization. 29,37,39 Koc et al 39 found that although treatment with CY plus G-CSF resulted in greater stem cell yield than did treatment with GM-CSF plus G-CSF, it also caused greater morbidity.…”
Section: G-csf In Conjunction With Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with mobilization regimens using G-CSF alone, chemomobilization is associated with increased morbidity, greater risk of infection, more hospital admissions, transfusions, antibiotic therapy and considerably greater cost overall. 29,[39][40][41][42] Although treatment-related mortality is rare, significant morbidity related to neutropenia that can often require hospitalization has been described, and many reports point to greater resource utilization with chemomobilization than with cytokine-alone mobilization. 29,37,39 Koc et al 39 found that although treatment with CY plus G-CSF resulted in greater stem cell yield than did treatment with GM-CSF plus G-CSF, it also caused greater morbidity.…”
Section: G-csf In Conjunction With Chemotherapymentioning
confidence: 99%
“…29,39 As a result, this mobilization strategy requires increased resource use, hospitalizations, transfusions and the use of antibiotic therapy. 29,[39][40][41][42] Furthermore, variation among individual responses to chemomobilization can result in irregular collection schedules that can increase resource utilization and potentially delay transplantation. 43,44 The utility of all current mobilization regimens is limited by their high failure rates, which are estimated to be from 5 to 30%, regardless of the approach.…”
Section: Introductionmentioning
confidence: 99%
“…PBSC were infused on day 0 and patients received standard supportive-care measures as previously described. [20][21][22] Toxicities were scored using National Cancer Institute clinical toxicity criteria. 23 No maintenance therapy was employed.…”
Section: Methodsmentioning
confidence: 99%
“…22 Two patients were mobilized with G-CSF alone. Responses after initial therapy and mobilization are shown in Table 2 by DurieSalmon stage; responses by ISS stage were similar except that none of the ISS stage three patients achieved CR or nCR.…”
Section: Patientsmentioning
confidence: 99%
“…60mg/m 2 plus G-CSF 10 μg/kg/day was successful in mobilizing PBPC from myeloma patients. However, toxicity was notable and duration of mobilization was longer compared with CY 3 g/m 2 (16.5 days vs 10 days) (Gupta et al, 2005). Melphalan is a highly effective anti-myeloma drug but due to its stem cell toxicity, it is neither used for PBSC mobilization, nor recommended as an initial therapy for patients elligible for AHCT.…”
Section: Chemomobilizationmentioning
confidence: 99%